2017
DOI: 10.1111/ajt.14031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anastomosis Time During Kidney Transplantation on Graft Loss: A Eurotransplant Cohort Study

Abstract: Recent studies raised the concern that warm ischemia during completion of vascular anastomoses in kidney implantation harms the transplant, but its precise impact on outcome and its interaction with other risk factors remain to be established. We investigated the relationship between anastomosis time and graft survival at 5 years after transplantation in 13 964 recipients of deceased donor solitary kidney transplants in the Eurotransplant region. Anastomosis time was independently associated with graft loss af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 24 publications
5
48
3
Order By: Relevance
“…Interestingly, warm ischaemic time was not associated with graft outcomes in our study. Anastomosis time did not have a significant impact on duration of DGF or longer term graft outcomes, though this association has been demonstrated in a recent large study [42].…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, warm ischaemic time was not associated with graft outcomes in our study. Anastomosis time did not have a significant impact on duration of DGF or longer term graft outcomes, though this association has been demonstrated in a recent large study [42].…”
Section: Discussionmentioning
confidence: 63%
“…The availability of a reliable large registry in Eurotransplant would contribute to improved patient management within its own region and current data are already being used for this purpose. 37,38 Furthermore, it creates the potential to facilitate the conduct of international donor management and preservation trials when primary outcome measures are captured in a registry, as was done recently by Niemann et al…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Compared with DBD donors, longer warm ischemia times after cardiac arrest in DCD donor reduce oxygen and nutrient supply to the tissues, leading increased IRI and reduced kidney quality. A recent study reported that greater warm ischemia times are associated with higher rates of graft failure and mortality after kidney transplantation (6, 7). IRI can also lead to progressive graft dysfunction with chronic fibroinflammatory changes that impacts long-term graft survival (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that greater warm ischemia times are associated with higher rates of graft failure and mortality after kidney transplantation. 6,7 IRI can also lead to progressive graft dysfunction with chronic fibroinflammatory changes that impact longterm graft survival. 8,9 It is therefore essential to develop strategies to prevent or ameliorate IRI and improve the quality of DCD allografts.…”
Section: Introductionmentioning
confidence: 99%